Adverse events associated with androgen receptor signaling inhibitors in the treatment of prostate cancer: A systematic review and network meta-analysis. Issue 28 (1st October 2022) - Cao, Brent; Kim, Melissa; Reizine, Natalie Marie; Moreira, Daniel
Abstract : 317 Background: Androgen receptor signaling inhibitors (ARSi) are emerging as standard treatments for prostate cancer across the disease spectrum. With multiple available agents approved, comparing adverse effects between different therapies may guide clinical decision-making. The purpose of this meta-analysis was to compare adverse events (AE) and serious adverse events (sAE) between the ARSi drugs abiraterone, apalutamide, darolutamide, and enzalutamide. Methods: PubMed, Web of Science, Embase, and Clinicaltrials.gov were searched for double-blind, randomized controlled trials for ARSi therapy in the treatment of prostate cancer (both metastatic and non-metastatic settings). Two independent teams extracted AE and sAE data. Studies were synthesized using R with the "Netmeta" package. Results: Thirteen double-blinded, randomized trials of abiraterone, apalutamide, darolutamide or enzalutamide were included in this study. The relative risk ratio (RR) of the most common any-grade AE compared to placebo was highest in enzalutamide with a RR of 1.30 (95% confidence interval [CI], 1.13-1.50), followed by apalutamide (1.20, [0.95-1.53]), abiraterone (1.19, [0.98-1.44]), and darolutamide (1.17, [0.83-1.65]). The risk of any sAE was highest in darolutamide (1.80, [0.91-3.57]), followed by apalutamide (1.75, [1.07-2.87]), abiraterone (1.56, [1.08-2.25]), and enzalutamide (1.57, [1.18-2.09]). For overall ARSi analysis, special sAE of interest included acute coronary syndrome, arrhythmia, and seizure, for which ARSi therapy was associated with an odds ratio (OR) of 2.85 (1.65-4.91), 1.75 (1.25-2.44), and 1.31 (0.57-3.00) respectively. Amongst themselves, enzalutamide had the highest risk of cardiovascular AE compared to non-enzalutamide ARSi (RR = 1.77, [1.42-2.20], p < 0.05). Abiraterone had the lowest risk of musculoskeletal AEs compared to non-abiraterone ARSi (0.79, [0.70-0.88], p < 0.05). No significant differences existed in the other domains of interest. Conclusions: ARSi therapy was associated with a higher risk of AE and sAE in various domains compared to placebo. Our findings suggest that the side-effect profiles of ARSis do not significantly differ except in the case of increased cardiovascular risk with enzalutamide and decreased musculoskeletal risk with abiraterone. This data may aid clinicians in determining personalized therapeutic options for their patents based on side effect profiles.